ASSESSING THE FUTURE OF CAPITAL MARKET AND INVESTMENT CLIMATE IN INDONESIA: A SCENARIO PERSONARRATIVE METHOD APPROACH - Aulia Muhammad, Adhimas
The role of the capital market is essential to the development of a country, as it has a positive relationship with economic growth. However, the effort to develop a sustainable capital market may be challenged with the uncertainties, such as a pandemic, political turmoil, and even investors’ behavior. Therefore, this research purpose is to unveil the future of the Indonesian capital market with the implications and the options for the stakeholders, including investors, to develop a best practice capital market. The scenario personarrative method is used in this research as they can complement each other by signifying the options to the different types of investors. Through the analyses, the government’s political direction and regulator ability play an important role to shape the Indonesian capital market. In addition to that, ten highlighted key driving forces are identified to create four-transformative scenarios: (1) Thin bull in the pastureland, (2) Facing torero in the bullring, (3) Train the circus bull, and (4) World-champion bull. These scenarios are not a single projection and keep iterating until 2030. On the other hand, eight personas through the cluster analysis method using Gower’s distance are also described with each of the unique characteristics that consist of the sensitivity toward pandemic and political events, the volatility of the market, intention toward the regulation, environment, emerging trend, risk profile, and irrational behavior. In the end, 32 behavior narratives are constructed based on the four scenarios and eight personas, as well as the options that significantly affect the different personas to be considered by the actors. Therefore, it is recommended that the stakeholders carefully consider their decisionmaking to ensure that the Indonesian capital market can achieve the world-champion bull scenario in 2030.